Digital signal compression : principles and practice - Pearlman, William A.; Said, Amir. (Cambridge ; New York : Cambridge University Press, 2011)
"With clear and easy-to-understand explanations, this book covers the fundamental concepts and coding methods of signal compression, whilst still retaining technical depth and rigor. It contains a wealth of illustrations, step-by-step descriptions of algorithms, examples and practice problems, which make it an ideal textbook for senior undergraduate and graduate students, as well as a useful self-study tool for researchers and professionals. Principles of lossless compression are covered, as are various entropy coding techniques, including Huffman coding, arithmetic coding and Lempel-Ziv coding. Scalar and vector quantization and trellis coding are thoroughly explained, and a full chapter is devoted to mathematical transformations including the KLT, DCT and wavelet transforms. The workings of transform and subband/wavelet coding systems, including JPEG2000 and SBHP image compression and H.264/AVC video compression, are explained and a unique chapter is provided on set partition coding, shedding new light on SPIHT, SPECK, EZW and related methods"--
Machine generated contents note: 1. Motivation: the importance of compression; 2. Book overview; 3. Principles of lossless compression; 4. Entropy coding techniques; 5. Lossy compression of scalar sources; 6. Coding of sources with memory; 7. Mathematical transformations; 8. Rate control in transform coding systems; 9. Transform coding systems; 10. Set partition coding; 11. Subband/wavelet coding systems; 12. Methods for lossless compression of images; 13. Color and multi-component image and video coding; 14. Distributed source coding.
Includes bibliographical references and index.
Keywords: Data compression (Telecommunication); Signal processing